Relationship between dryland strength and swimming performance: Pull-up mechanics as a predictor of swimming speed - Perez-Olea, J. I.; Valenzuela, P. L.; Aponte, C.; Izquierdo, M. (The Journal of Strength and Conditioning Research, 2018)
This study aimed to examine the validity of the countermovement jump (CMJ) and the pull-up exercise as predictors of swimming performance. Twelve young male swimmers (Mean ± SD, 19 ± 3 years; 75 ± 10 kg; 180 ± 6 cm) with a homogenous level of performance (50-m freestyle time [50F]: 26.41 ± 1.44 seconds, coefficient of variance: 5.5%) participated in this study. Subjects performed a test of a single pull-up (PU) and a test of maximum number of pull-ups until muscular failure (PUF), and the mechanics of the ascending phase were recorded using a lineal force transducer. The height reached in a single CMJ test and the mean height during 30 consecutive CMJs were also determined. The swimmers' 50-m leg-only swimming time (50L) was also registered. The 50F time was strongly correlated with different variables of the PU (r = -0.76 to -0.80; p = 0.05) and PUF test (r = -0.64 to -0.88; p = 0.05), but not with the number of pull-ups performed. A significant relationship between 50F and 50L was observed (r = 0.78; p = 0.05), with no relationship between the CMJ tests and swimming performance. Furthermore, multiple linear regression showed that 50L and the relative loss of velocity during the PUF test accounted for 84% (p < 0.001) of the 50F performance variance. This study shows the validity of the analysis of pull-up mechanics and 50L to predict short-distance swimming performance in trained swimmers, confirming the importance of upper-limb strength and leg kick on this sport.